ANALISIS RESPON PENAWARAN DAGING SAPI POTONG DI PASAR SIBUHUAN, KABUPATEN PADANG LAWAS, PROVINSI SUMATERA UTARA - Aflahun Fadhly Siregar; Salsabila Salsabila; Muhammad Alqamari (JURNAL AGROTEKNOSAINS, 2022)
Livestock is one of the agricultural sub-sectors that are useful for consumers to fulfill protein needs. So with that there is a need for development in the livestock sector. In Indonesia, various types of animals are raised, including cattle, buffalo, goats, chickens, ducks, and other animals. Sibuhuan market is an area where consumers can get their household needs, especially beef beef. The market that provides beef beef needs only twice a week, namely on Sundays when the public is off for activities and Monday as a big time at Sibuhuan Market.